2018
DOI: 10.1002/jsfa.8874
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modeling for estimating glucosinolate content in Chinese cabbage by growth conditions

Abstract: To our knowledge, this study presents the first statistical model for evaluating glucosinolate content, suggesting a useful methodology for designing glucosinolate-related experiments, and optimizing glucosinolate content in Chinese cabbage cultivation. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Cabbage is widely planted in China, especially in Southern China, which has approximately half of the total cabbage-growing area. Cabbage is an important cash crop, the consumption of which also ranks fi rst among all vegetables in China (Kim et al, 2018;Xiang et al, 2018). Cabbage has a large demand for water and fertilizer; the fertilizer use in China's cabbage production is about 454.63 kg/ha, and in cabbage production, the fertilizer is easy to lose, so the partial and excessive fertilization phenomenon is serious (McKeown et al, 2010).…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…Cabbage is widely planted in China, especially in Southern China, which has approximately half of the total cabbage-growing area. Cabbage is an important cash crop, the consumption of which also ranks fi rst among all vegetables in China (Kim et al, 2018;Xiang et al, 2018). Cabbage has a large demand for water and fertilizer; the fertilizer use in China's cabbage production is about 454.63 kg/ha, and in cabbage production, the fertilizer is easy to lose, so the partial and excessive fertilization phenomenon is serious (McKeown et al, 2010).…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…Statistical modeling is an effective tool for quantifying the relationship between dependent and independent variables by the statistical significance of their correlations (Kim et al, 2016). Kim et al (2018) developed a statistical model for glucosinolate content in Chinese cabbage using a secondorder multi-polynomial equation with growth duration and temperature as independent variables. In this study, the model structure was determined according to the linear pattern of phenolic accumulation with UV-B dose as shown in the results from previous studies (Dou et al, 2019;Yoon et al, 2021a) or quadratic pattern with leaf group as shown in Figure 6 and the results from a previous study (Yoon et al, 2021b).…”
Section: Predicting Models Of Phenolic Content In Three-dimensional P...mentioning
confidence: 99%
“…Studies have shown that the main factor affecting the content and composition of GSL is genotype, and the content and composition of GSL were different among different species and varieties ( SzydłOwska-Czerniak et al, 2011 ; Wiesner et al, 2013b ; Rhee et al, 2020 ; Jeon et al, 2022 ). Temperature, light quality, mechanical injury, and insect feeding can affect GSL biosynthesis and component content ( Pedreno et al, 2017 ; Kim D. et al, 2018 ; Lin et al, 2022 ). Moreover, biosynthesis of GSL is also influenced by plant hormones, plant growth regulators, chemical fertilizers, pesticides, metal ions, gas, etc.…”
Section: Introductionmentioning
confidence: 99%